Acute Pancreatitis and Ileus Postcolonoscopy - Hin Hin Ko; Trevor Jamieson; Brian Bressler (Canadian Journal of Gastroenterology)
Postpolypectomy bleeding and perforation are the most common complications of colonoscopy. A case of acute pancreatitis and ileus after colonoscopy is described. A 60-year-old woman underwent a gastroscopy and colonoscopy for investigation of iron deficiency anemia. Gastroscopy was normal; however, the colonoscope could not be advanced beyond the splenic flexure due to a tight angulation. Two polypectomies were performed in the descending colon. After the procedure, the patient developed a distended, tender abdomen. Bloodwork was remarkable for an elevated amylase level. An abdominal x-ray and computed tomography scan showed pancreatitis (particularly of the tail), a dilated cecum and a few air-fluid levels. The patient improved within 24 h of a repeat colonoscopy and decompression tube placement. The patient had no risk factors for pancreatitis. The causal mechanism of pancreatitis was uncertain but likely involved trauma to the tail of the pancreas during the procedure. Our patient developed ileus, likely secondary to pancreatitis. The present case is the first report of clinical pancreatitis and ileus associated with colonoscopy.